Mutation scanning of exon 20 of the BRCA1 gene by high-resolution melting curve analysis - Vorkas,P.A.; Christopoulos,K.; Kroupis, C.; Lianidou,E.S. (Clin.Biochem., 2010)
OBJECTIVES: 5382insC frameshift mutation along with 5331G>A (G1738R) missense mutation, both found in exon 20 of the BRCA1 gene, are relatively frequent among the Greek breast and ovarian cancer population (46%). Our goal was to develop a novel, reliable and rapid genotyping/scanning method for mutation detection of the exon 20 of the BRCA1 gene, using high-resolution melting curve analysis. DESIGN AND METHODS: The developed methodology was based on real-time PCR and high-resolution melting curve analysis in the presence of LCGreen I dye. Two amplicons on the exon 20 of BRCA1 gene were designed (157 bp and 100 bp), one flanking the exon's boundaries, and one embracing the 5382insC mutation. Our methodology was first optimized and validated by using genomic DNA samples with the 5382insC and 5331G>A (G1738R) mutations and wild-type. In total, the developed methodology was applied on 90 peripheral blood and 127 formalin-fixed paraffin-embedded breast tissue samples. RESULTS: Sensitivity studies with gDNA isolated from peripheral blood showed that mutated DNA could be reliably detected in the presence of wild-type DNA at 5% and 0.5% ratio with the larger and the smaller amplicon, respectively. By using the developed methodology we successfully identified 5382insC, 5331G>A and 5370C>T (R1751X) mutations, in genomic DNA isolated from peripheral blood samples and 5382insC mutation in two breast tumors, as verified by DNA sequencing. CONCLUSIONS: The combination of real-time PCR and high-resolution melting curve analysis provides a cost-efficient, simple and rapid approach to successfully scan exon 20 of BRCA1 gene for these clinically important and frequent mutations
DA - 20100127 IS - 1873-2933 (Electronic) IS - 0009-9120 (Linking) LA - eng PT - Evaluation Studies PT - Journal Article PT - Research Support, Non-U.S. Gov't SB - IM
Keywords: analysis; Blood; Breast Neoplasms; DNA Mutational Analysis; Exons; Female; Frameshift Mutation; Genes,Brca1; Genetic Predisposition to Disease; genetics; Genotype; Greece; Humans; Mutation; Mutation,Missense; Nucleic Acid Denaturation; Ovarian Neoplasms; Reproducibility of Results; Sensitivity and Specificity